The Influence of Elevated Iodide Supply on the Autonomously Functioning Thyroid Gland - Waters, W.; Kutzim, H.; Wellner, U. (Nuklearmedizin - NuclearMedicine, 1984)
A pharmacokinetic two-compartment model of iodine metabolism has been established on the basis of data from the literature and our own experimental investigations. By this model it is possible to estimate the effects either of prolonged elevation of iodide supply or of a single administration of a high dose of inorganic iodide in the presence of autonomously functioning thyroid tissue. Prolonged elevation of iodide supply in regions of iodine deficiency will cause manifest hyperthyroidism in many cases of thyroidal autonomy (cases with facultative hyperthyroidism). The administration of a single high dose of iodide, as it is proposed for the situation of an accident in a nuclear power station (100 mg Nal) in order to reduce the radiation burden to the surrounding population, carries almost no risk in cases of thyroid autonomy.